ANALISIS RASIO PROFITABILITAS PADA KEPUTUSAN PENERBITAN RIGHT ISSUE - Irham Fahmi (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2012)
This research want see about condition campany in perspective profitability ratio in beforeand after right issue. Decision right issue is a decision in make company will be recovery or healtagain, and future effect to profitability company will increase.The result in research is show condition company after right issue more better if comparebefore right issue. In statistic test with Wilcoxon Signed Ranks Test we can see insignificant inprofitability before and after right issue (p-value > 0,05). The average before right issue in 1999 is1,0732 and after right issue is 0,7030. The found of right issue can make company have programinvestment or make new product.Source financial of right issue more safe if compare of banking, especially risk managementperspective. Right issue is fund of internal company, especially of preventive right.